Blunted responses to reward in remitted post‐traumatic stress disorder. Issue 8 (11th June 2015) - Kalebasi, Nilufer; Kuelen, Eveline; Schnyder, Ulrich; Schumacher, Sonja; Mueller‐Pfeiffer, Christoph; Wilhelm, Frank H.; Athilingam, Jegath; Moergeli, Hanspeter; Martin‐Soelch, Chantal
Abstract Background Recent evidence suggests blunted responses to rewarding stimuli in patients with post‐traumatic stress disorder (PTSD). However, it is not clear whether these alterations in reward processing normalize in remitted PTSD patients. Methods We tested behavioral and physiological responses to monetary reward in a spatial memory task in 13 accident survivors with remitted PTSD, 14 accident survivors who never had PTSD, and 16 nontrauma‐exposed subjects. All accident survivors were recruited from two samples of severely physically injured patients, who had participated in previous prospective studies on the incidence of PTSD after accidental injury approximately 10 years ago. Reaction time, accuracy, skin conductance responses, and self‐reported mood were assessed during the task. Results Accident survivors who never had PTSD and nontrauma exposed controls reported significantly higher positive mood in the reinforced versus nonreinforced condition (P < 0.045 and P < 0.001, respectively), while there was no effect of reinforcement in remitted PTSD subjects. Conclusions Our findings suggest an alteration of the reward system in remitted PTSD. Further research is needed to investigate whether altered reward processing is a residual characteristic in PTSD after remission of symptoms or, alternatively, a preexisting risk factor for the development of PTSD after a traumatic event.